Electron g-factor study in Ga1-xInxAsySb1-yGaSb and GaSb-Ga1-xInxAsySb1-y-GaSb quaternary alloy semiconductor spherical quantum dots (2011)
Within an interpolation scheme, we have determined the electron g-factor and the Kane interband energetic parameter of Ga1 − xInxAsySb1 − y–GaSb semiconductors quaternary alloy and used them to determine the electron g-factor in GaSb–Ga1 − xInxAsySb1 − y–GaSb spherical quantum dots (SQDs) as well as to calculate the Landau levels. In the low-dimensional systems a framework of an eight-band effective-mass model in which the contribution of the conduction remote bands and the mixing between the conduction band Γc6 and the valence bands Γv8 and Γv7 states are considered. Our results show that the dependence of the bulk electron g-factor as a function of x can be fit with a cubic polynomial. We have established a relation between the electron g-factor and both the radius and the indium concentration in GaSb–Ga1 − xInxAsySb1 − y–GaSb SQDs. For these quaternary SQDs with a parabolic confining potential we have found that the difference between the electron energy levels corresponding to spin-up and spin-down states is larger (∼ 10 meV) than the corresponding states in GaAs–(Ga, Al)As quantum wells (QWs) (∼ 0.2 meV) of comparable dimensions and increases with the applied magnetic field